The Fan Use of Football Club Official Media (Descriptive Study of The Use of PS Sleman Official Media) - Narayana Mahendra Prastya (Komunikator, 2020)
This research analyzed the use of official media of the Indonesia football club used by the fans. The context of official media is the official club website and official social media account of the club. The football club needs to manage the official media (especially in the internet platform) to build interaction and relationships with its fans. An engaging interaction and relationship with fans will strengthen the fans' loyalty to the club. This research used qualitative methods, with an interview in Focus Group Discussion (FGD) format as the data collecting technique. The informants were the university student aged 18-21 years old and the fans of PS Sleman (written with PSS hereafter) football club. The number of participants was eight. FGD held in May 2017, when in that year, PSS became the only Liga 2 contestant that had a verified Twitter account. Results showed that although the informants used the PSS official media, they were unsatisfied because the PSS official media lacked interactivity, updating information, and the completeness of the information. To fulfill their expectations, informants use the unofficial media, usually the fans-driven media. For informants, the unofficial media performance was much more significant than the PSS official media